The use of scripture in Swahili tracts by Muslims and Christians in East Africa - Chesworth, John Anthony (University of Birmingham, 2008)
This research assesses the use of scripture in tracts published in Swahili in East Africa. The use of tracts for the propagation of religion is introduced through the work of Tract Societies in Britain and the use of Christian tracts in overseas missions. Printing in Arabic and the propagation of Islam through tracts is surveyed. The historical use of tracts by Christians and Muslims in East Africa, and Swahili as a religious language, are examined. In 2000 and 2001, Christian and Muslim tracts in Swahili were purchased from particular locations in Kenya and Tanzania. Of these, sixteen tracts, eight by Christians and eight by Muslims, were selected. The tracts use passages from the Bible and/or the Qur’an mainly for outreach purposes. They are described and analysed and scriptures within them recorded. Eighteen Biblical and Qur’anic passages that appeared in more than one tract were chosen. These scriptures, together with the interpretations of them within the tracts, are translated, presented thematically, analysed and compared. The research found differences between Christian and Muslim use of the passages, noting that the approach of most tracts is polemical, thus raising concerns that they may increase misunderstandings between Christians and Muslims in East Africa.
free